System relations in the thematic group of vocabulary is on denotation of man and its traits of the lower-Dnieper-steppe dialects (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with the phenomenon of synonymy and variation in the investigated lexics. Also stylistic potential of positive and negative marking lexems is cleared up.
Keywords: synonyms; synonymic raw; negative expressive colouring; phonetic variants; word-building variants; secondary nomination